An In Situ Synchrotron Radiation Grazing Incidence X-Ray Diffraction Study of Carbon Dioxide Corrosion - De Marco, R; Jiang, Z T; Pejcic, B; Poinen, E (Journal of The Electrochemical Society, 2005)
An in situ surface study of the carbon dioxide corrosion of mild steel has been undertaken using the tandem technique of mixed potential/synchrotron radiation-grazing incidence X-ray diffraction (SR-GIXRD). Long-term monitoring of the mixed potential showed there was an initial shift toward cathodic potentials attributable to preferential suppression of the cathodic half-reaction (viz., the reduction of carbonic acid), probably due to the formation of an adlayer of corrosion product physically blocking the cathodic reaction sites during the uniform corrosion of mild steel. Subsequently, the mixed potential displayed a gradual shift to anodic potentials, symbolizing the preferential suppression of the anodic half-reaction as the primary corrosion products [viz., Fe2(OH)2CO3, Fe2O2(CO3), Fe6(OH)12(CO3), and Fe6(OH)12(CO3)·2H2O] acquired a sufficient thickness to physically block the interface against further corrosion. Nevertheless, the corrosion product continues to grow over time, indicating that the corrosion product is discontinuous and porous, allowing the ingression of electrolyte to enable the further corrosion of the mild steel. This research has important ramifications for the field of corrosion research; it should enable researchers to develop improved methods of chemical inhibition by using compounds that can actually bind to the newly postulated corrosion products on mild steel.